2007
DOI: 10.1080/09553000701420582
|View full text |Cite
|
Sign up to set email alerts
|

Low dose X-radiation adaptive response in spleen and prostate ofAtmknockout heterozygous mice

Abstract: Being heterozygous for a knockout mutation in the Atm gene does not affect the endogenous pKZ1 inversion frequency, the inversion response to single low radiation doses used here, or the induction of a radiation adaptive response for inversions in pKZ1 mouse spleen or prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
0
17
1
Order By: Relevance
“…The gene Atm encodes ATM, which is a member of the PI-3 kinase protein family, and it plays a crucial role in the signal transduction network that modulates cell-cycle checkpoints, DNA repair, and other cellular responses to DNA damage. This gene is also responsible for ataxia telangiectasia (AT) [35]. The Atm KO mice present an osteopenic phenotype as early as 10 weeks old, apparently due to decreased bone marrow-derived mesenchymal progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…The gene Atm encodes ATM, which is a member of the PI-3 kinase protein family, and it plays a crucial role in the signal transduction network that modulates cell-cycle checkpoints, DNA repair, and other cellular responses to DNA damage. This gene is also responsible for ataxia telangiectasia (AT) [35]. The Atm KO mice present an osteopenic phenotype as early as 10 weeks old, apparently due to decreased bone marrow-derived mesenchymal progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…The role of p53 (TP53) is not clearly established and seems to depend on the cell type studied and the biological end point used to measure the radioadaptive response (7,8). Both ATM homozygous and heterozygous mutants demonstrated an adaptive response to radiation-induced chromatid breaks (9) and chromosomal inversion frequency (10). Nevertheless, the radioadaptive response, and therefore low-dose response, may involve more than DNA repair pathways.…”
Section: Introductionmentioning
confidence: 98%
“…While the 10 mGy X-radiation dose may have been too low to elicit any detectable changes to DNA methylation, we have previously demonstrated that mice irradiated with a single whole body dose of 10 mGy given at the same dose rate used here (13.9 mGy/min) induces a radioadaptive response causing significant changes in chromosomal inversion frequency in spleen and prostate [53], [54], [94][96]. A single dose of 10 mGy has also been shown to induce a radioadaptive response for a range of other endpoints [34], [36], [97][99].…”
Section: Discussionmentioning
confidence: 83%
“…This is predominantly due the widespread distribution of these elements, and the evidence that increased transposition activity of these elements due to a loss of methylation can increase the overall genomic instability associated with age [13][16], [50]–[52]. There is also evidence that methylation of the murine homologues, L1, B1 (Alu) and IAP (LTR), can display aberrant methylation in aging mice [10], [12], [53]. Based on both the human and mouse studies, we chose to utilise the L1, B1 (Alu homologue) and IAP (murine LTR) elements to monitor age or X-ray induced changes to methylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation